The influence of thermal and acid modification on the potential application of Jegłowa kaolin in cosmetic formulations - Czarnecka-Skawrek, Anna; Rożek, Agnieszka (Gospodarka Surowcami Mineralnymi – Mineral Resources Management, 2026)
The aim of this study was to develop a clay-based mineral material with enhanced sorption properties suitable for application as an active ingredient in cosmetic formulations. Kaolin samples from the Jegłowa deposit were subjected to structural modifications through thermal treatment at 300, 600, and 900°C, as well as acid activation using a 4 M HCl solution. The resulting materials were assessed for microbiological quality in accordance with the ISO/DIS 17516 standard. In addition, mineralogical composition (X-ray diffraction and thermal analysis), specific surface area, pore structure, and sorption properties (gas porosimetry, SEM) were characterized to evaluate the influence of the type and intensity of modification on the functional properties of kaolin. Thermal modification at 600°C induced decomposition processes, resulting in a reduction in structural order and a decrease in specific surface area, which consequently limited the material’s sorption capacity. In contrast, acid activation led to a significant increase in the specific surface area of kaolin, which is advantageous for sorption processes occurring at the interface between the modified clay material and the epidermal layers. Microbiological analyses revealed that unmodified kaolin samples did not meet the requirements specified in the PN-EN ISO 17516 standard. Satisfactory microbiological quality was achieved exclusively in samples subjected to combined thermal and acid modification. Based on these results, it was concluded that unmodified Jegłowa kaolin can be incorporated into cosmetic formulations only in combination with antimicrobial agents to ensure compliance with microbiological quality requirements of the final product.